Exploring Critical Effect of Knowledge Inflows and Absorptive Capacity on Product Innovation - Raisal, Ismail; Kumar Tarofder, Arun; Silva, DAC. (Opción, 2019)
The primary aim of this study is to measure the effect of external knowledge inflows and absorptive capacity on product innovation through innovative culture. Structural Equation Modeling was used by PLS software as a method and results indicated that all hypothesis were accepted except the direct effect of external knowledge on product innovation. In conclusion, ACAP is highly important to creating an organizational learning culture in the forms of encouraging teamwork, creativity, and innovation, doing things in new ways, individually approaching the job, and improving communication between departments